Migrating Enterprise Storage to SSDs: Analysis of Tradeoffs - Narayanan, Dushyanth; Thereska, Eno; Donnelly, Austin; Elnikety, Sameh; Rowstron, Ant (Proceedings of EuroSys 2009, 2009)
Recently, ﬂash-based solid-state drives (SSDs) have become standard options for laptop and desktop storage, but their impact on enterprise server storage has not been studied. Provisioning server storage is challenging. It requires optimizing for the performance, capacity, power and reliability needs of the expected workload, all while minimizing ﬁnancial costs. In this paper we analyze a number of workload traces from servers in both large and small data centers, to decide whether and how SSDs should be used to support each. We analyze both complete replacement of disks by SSDs, as well as use of SSDs as an intermediate tier between disks and DRAM. We describe an automated tool that, given device models and a block-level trace of a workload, determines the least-cost storage conﬁguration that will support the workload’s performance, capacity, and fault-tolerance requirements. We found that replacing disks by SSDs is not a cost effective option for any of our workloads, due to the low capacity per dollar of SSDs. Depending on the workload,the capacity per dollar of SSDs needs to increase by a factor of 3–3000 for an SSD-based solution to breakeven with a disk based solution. Thus, without a large increase in SSD capacity per dollar, only the smallest volumes, such as system boot volumes, can be cost-effectively migrated to SSDs. The beneﬁt of using SSDs as an intermediate caching tier is also limited: fewer than 10% of our workloads can reduce provisioning costs by using an SSD tier at today’s capacity per dollar, and fewer than 20% can do so at any SSD capacity per dollar. Although SSDs are much more energy-efﬁcient than enterprise disks, the energy savings are outweighed by the hardware costs, and comparable energy savings are achievable with low-power SATA disks.